The Relationship Between Exclusive Breastfeeding Counseling and Food Restrictions Culture and the Success of Exclusive Breastfeeding at the WARA Community Health Center in Palopo City - Kasmayani, Kasmayani; Hastuty, Dewi; Yanti, Yuniar Dwi; Adeliana, Adeliana; Jamilda, Nur Gita; Khatimah, Husnul; Akhfar, Kurniati (Jurnal Midwifery, 2026)
Introduction: Breast milk (ASI) is the primary source of nutrition that influences the nutritional status and health of infants. The government has set a target of 50% for exclusive breastfeeding coverage for infants aged 0-6 months, but some regions still have low breastfeeding coverage. Insufficient breast milk production is the most common complaint expressed by postpartum mothers and is a contributing factor to the failure of exclusive breastfeeding. The purpose of this study was to determine the relationship between exclusive breastfeeding education and cultural food restrictions on the success of exclusive breastfeeding. Research Method: An analytical observational design with a cross-sectional approach. The study population was all 35 breastfeeding mothers with infants aged 6 months and older residing in the Wara Community Health Center (Puskesmas) working area in Palopo City. Sampling was conducted using purposive sampling, considering inclusion and exclusion criteria. Inclusion criteria: Breastfeeding mothers with infants aged 6 months and older; 2) Willingness to participate in all stages of the four-week training; 3) No psychological disorders or serious medical conditions that could interfere with breastfeeding. Exclusion criteria: 1) Mothers who have premature babies with a gestational age of <34 weeks; and Babies who have congenital abnormalities that affect the ability to breastfeed. The sample size in this study according to Slovin can be determined by the formula. So the sample in this study was 35 respondents. Data collection was carried out using a questionnaire. The collected data were then processed and analyzed using the SPSS statistical program analyzed with the Chi Square test. Research Results: Based on the results of the study using the Chi-Square statistical test, it shows a p value = 0.000, which is statistically very significant (p <0.05), so it can be concluded that there is a relationship between Exclusive Breastfeeding counseling and Exclusive Breastfeeding. The results of the bivariate chi square analysis showed a p value = 0.000 which is statistically very significant (p <0.05), indicating a relationship between the culture of food taboos and the success of Exclusive Breastfeeding. Conclusion: There is a relationship between exclusive breastfeeding counseling and exclusive breastfeeding at the Wara Health Center, Palopo City in 2026 and there is a relationship between cultural food taboos and exclusive breastfeeding at the Wara Health Center, Palopo City in 2026.